The incidence and associated risk factors of injury in professional golfers - Visagie, Jacobus A (Department of Health and Rehabilitation Sciences, 2022)
Background Golf has become an immensely popular sport around the globe. The competitiveness of golf and the livelihood it provides to the professional players has led to copious amounts of training and individuals pushing the physiological limits of their bodies in order to play the perfect stroke. Therefore, this population is prone to injury, with prevalence of injury as high as 60%. Literature has shown the lower back to be the most frequently injured anatomical region. There is still a lack of evidence regarding the cause of these high injury rates amongst the professional golfers. Furthermore, investigation of the incidence or associated risk factors of injury has not been conducted amongst the professional players from South Africa. The importance of identifying associated risk factors of injury in this population is of vital importance as this could potentially influence their livelihood directly. Aim The aim of this study was to investigate the incidence of overall and region-specific injury in professional South African golfers. Furthermore, the potential risk factors leading to these injuries were investigated. Results 17 participants (60.7%) reported an injury and a total of 23 index injuries were documented. The incidence rate of injury was 3.27/1000hrs of playing golf. The most frequently injured anatomical regions were the lower back and shoulder (26.1%). There were statistically significant differences in the joint range of motion of horizontal adduction of the leading shoulder (p=0.04) between the group reporting an injury compared to the group with no injury. Furthermore, statistically significant differences were found in decreased range of motion of internal rotation of the trailing shoulder (p=0.04) in the group with a shoulder injury compared to the group without a shoulder injury, and as well as in the group with hip pain compared to the group without hip pain (p=0.048). The group with hip injuries also showed a decreased range of motion of external rotation of the leading hip (p=0.048). Furthermore, a decreased range of motion of external rotation of the leading shoulder had a statistically significant difference (p=0.026) between the group that reported a wrist injury and the group that did not. The group that reported lumbar spine injuries had significant decreased range of motion of external rotation in the trailing shoulder (p=0.031), horizontal adduction of the trailing shoulder (p=0.015), horizontal adduction of leading shoulder (p=0.029), and internal rotation of the leading hip (p=0.003). Furthermore, the uninjured group spent more hours on total training in the eleventh week, which also presented a statistically significant difference (p=0.03). Conclusion In conclusion, injuries amongst professional golfers are common and the anatomical regions most affected are the lower back and the shoulder. Improving the range of motion of the leading and trailing shoulder horizontal adduction, trailing shoulder internal and external rotation, and internal rotation of the leading hip range of motion by means of mobility exercises could potentially minimize the risk of sustaining injury amongst professional golfers. Training volume did not present a statistically significant difference between the injured and uninjured groups in overall or region-specific injuries.